(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The popularity of Electric Vehicles (EVs) is witnessing a notable surge due to several factors, including reduced costs and an increased awareness of climate and environmental issues. This manuscript provides a thorough analysis of the progress in EVs, focusing on trends in battery technology, charging methods, and the emerging research challenges and opportunities. Specifically, it evaluates the global market landscape for EVs and their potential future. Given that the battery is a crucial component of EVs, this paper presents a detailed review of battery technologies, from Lead-acid batteries to Lithium-ion. Additionally, we examine the various standards governing the EV charging process, along with proposals concerning power control and battery energy management. In conclusion, we outline our viewpoint on the expected advancements in this field in the near future, as well as the research opportunities that remain available for both industry and academia.